2009
DOI: 10.1074/jbc.m109.012393
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Ambroxol as an Enzyme Enhancement Agent for Gaucher Disease

Abstract: Gaucher disease (GD), the most prevalent lysosomal storage disease, is caused by a deficiency of glucocerebrosidase (GCase). The identification of small molecules acting as agents for enzyme enhancement therapy is an attractive approach for treating different forms of GD. A thermal denaturation assay utilizing wild type GCase was developed to screen a library of 1,040 Food and Drug Administration-approved drugs. Ambroxol (ABX), a drug used to treat airway mucus hypersecretion and hyaline membrane disease in ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
303
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 291 publications
(313 citation statements)
references
References 66 publications
8
303
0
2
Order By: Relevance
“…ABX, a mixed-type inhibitor of GCase (Maegawa et al, 2009), has been shown to interact with both the active and non-active sites of GCase in a pHdependent manner. It has a theoretical advantage over other iminosugars because it does not require wash-out periods, which enables continued dosing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABX, a mixed-type inhibitor of GCase (Maegawa et al, 2009), has been shown to interact with both the active and non-active sites of GCase in a pHdependent manner. It has a theoretical advantage over other iminosugars because it does not require wash-out periods, which enables continued dosing.…”
Section: Discussionmentioning
confidence: 99%
“…In an experiment to examine the "chaperoning" half-life of ABX, GD fibroblasts were grown in medium containing 60μm ABX or DMSO (mock-treated) for 5 days (Maegawa et al, 2009). The cells were then "chased" for 8 days by replacing the ABX/DMSO-containing media with fresh media lacking the compounds and thereafter every other day.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, small molecular chaperones designed to cross the blood–brain barrier that are capable of increasing GCase activity are being investigated as a novel therapy for PD to decrease α‐synuclein levels 17, 18, 19, 20, 21, 22, 23, 24, 25…”
mentioning
confidence: 99%
“…Ambroxol was identified as a GCase chaperone after screening the library of US Food and Drug Administration–approved drugs with a thermal denaturation assay using wild‐type GCase 19. To date, 2 ambroxol studies using wild‐type mice or transgenic mice carrying a human transgene containing either N370S or L444P mutation failed to provide convincing evidence to determine whether ambroxol is capable of increasing GCase in the peripheral and neuronal tissues 23, 24.…”
mentioning
confidence: 99%
“…However, the ideal PC would bind tightest at the neutral pH of the ER and weakest or not at all at the acidic pH of the lysosome [11], e.g. Ambroxol for Gaucher Disease [12]. Like SRT, EET has the potential to treat the CNS, but is limited to a subgroup of "responsive" mutations.…”
Section: Introductionmentioning
confidence: 99%